2015
DOI: 10.1080/09540121.2015.1071768
|View full text |Cite
|
Sign up to set email alerts
|

Disease disclosure, treatment adherence, and behavioural profile in a cohort of vertically acquired HIV-infected adolescents. NeuroCoRISpeS study

Abstract: Perinatally-acquired HIV-infected adolescents showed significant psychosocial and behavioural health risks that should bring attention to prevention and health care programmes. An earlier disclosure to children could favour a better psychological adjustment and a better treatment adherence. Future studies are needed to assess the relationship between vertically acquired HIV-infection and hyperactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…The increased psychosocial problems in HIV-infected adolescents were consistent with a previous study which revealed that HIV-infected adolescents had scored a risk of emotional and behavioral problems, identified from the SDQ as 24.5% [11]. Stigmatization and discrimination may be one of the factors that these adolescents have experienced so that these could affect peer relationship and Prosocial behaviors [14,27].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The increased psychosocial problems in HIV-infected adolescents were consistent with a previous study which revealed that HIV-infected adolescents had scored a risk of emotional and behavioral problems, identified from the SDQ as 24.5% [11]. Stigmatization and discrimination may be one of the factors that these adolescents have experienced so that these could affect peer relationship and Prosocial behaviors [14,27].…”
Section: Discussionsupporting
confidence: 78%
“…In a cohort study, emotional and behavioral problems were found in 24.5% of HIV-infected adolescents [11]. Similarly, the prevalence of mental health problems was reported to be 29% in a study of children with perinatal HIV infection [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is common that perinatally HIV-infected youth started to be sexually active while still under the care of paediatric health services. [ 22 , 23 ] When analysed, perinatally HIV-infected youth have not always had an adequate knowledge about their disease. [ 23 ] Unprotected sexual intercourse may be not so uncommon, leading to unintended pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 , 23 ] When analysed, perinatally HIV-infected youth have not always had an adequate knowledge about their disease. [ 23 ] Unprotected sexual intercourse may be not so uncommon, leading to unintended pregnancies. [ 23 , 24 ] The discussions with HIV-infected adolescents may not focus only on the prevention of sexually transmitted infections but also on family planning.…”
Section: Discussionmentioning
confidence: 99%
“…This work is included in a prospective and ongoing cohort study (NeuroCoRISpe) to analyze the psychosocial, neurocognitive, and neuroimaging profile of vertically HIV-infected children. [26][27][28] This manuscript focuses on the cross-sectional assessment of their SQ.…”
Section: Participants and Proceduresmentioning
confidence: 99%